Analisis Pengaruh Brand Trust dan Perceived Quality terhadap Repurchase Intention melalui Brand Image sebagai Variabel Intervening: Studi pada Konsumen Produk Skincare Azarine di Kota Semarang - Debora Nathalia Amanda; Yoestini Yoestini (Faculty of Economics and Business Diponegoro University, 2026)
This research is driven by the rising trend in skincare use, which intensifies competition in Indonesia's skincare industry. This development is supported by growing public awareness of selfcare and by the role of social media, such as TikTok, in shaping consumer perceptions through product reviews and user experiences. On the other hand, the emergence of overclaim issues in Azarine serum products has raised consumer concerns about brand trust and product quality, potentially affecting brand image and repurchase intention. Therefore, this study aims to analyse the effect of Brand Trust and Perceived Quality on Repurchase Intention, with Brand Image as an intervening variable. Consumers aged 18 or older who reside in Semarang and have used Azarine skincare products within the last six months were selected as respondents in this study. The sample size of this study was 135 respondents. Data collection was conducted via online questionnaires with a 5-point Likert scale. The sampling technique used was non-probability purposive sampling. The data analysis method used to test the research model was Structural Equation Modelling (SEM) in AMOS 28. The results show that perceived quality has a positive and significant effect on brand image and repurchase intention. Brand trust does not have a significant effect on brand image, but it has a positive and significant effect on repurchase intention. In addition, brand image has been shown to have a positive and significant effect on repurchase intention, indicating that it plays a mediating role in the relationship between these variables and Repurchase Intention.